PAHLAWAN DAN PENJAHAT DALAM VISI RETORIS KEMENANGAN UMAT ISLAM PADA REUNI AKBAR PERSATUAN ALUMNI 212 TAHUN 2019 - Zahara, Elyan Nadian (Islamic Communication Journal, 2020)
The purpose of this study is to explain who were the Hero and Villains contributed to rhetorical vision’s legitimation and the shared meaning embraced in the Grand Reunion of Alumni Brotherhood (PA) 212 in 2019. Rhetorical vision is determined by the dominant character and symbolic cues embraced as shared meanings in a group. This study used qualitative approach, while the data was collected using virtual ethnography method and analyzed using Borman’s Fantasy Theme’s Analysis. From the results of the study it was found that the dominant character mentioned in the reunion as a hero was Habib Rizieq Shihab, while the characters named as criminals were those who were considered to have defamed Islam, such as Abu Janda, Ade Armando, Sukmawati Soekarno Putri and Viktor Laiskodat. The rhetorical vision carried out is Moslem’s victory. The grand reunion was held as an effort to urge the government to be more assertive and responsive to contemporary issues faced by Muslims in Indonesia.